Stalking: Cultural, Clinical, and Legal Considerations - Daileader, Celia R. (2000)
Crimes of violence against women are unique in their treatment by our culture and our system of legal justice. Both culturally and statutorily, victims of crimes which have historically been perpetrated against women, such as rape, domestic violence, and stalking have received significant focus. This article highlights cultural considerations and provides a statutory and case law analysis